Senegalese sole larvae growth and protein utilization is depressed when co-fed high levels of inert diet and Artemia since first feeding - Engrola, S. (2014)
A large effort has been dedicated in the past years to the development of nutritional balanced inert diets for marine fish larvae in order to suppress the nutritional deficiencies of live feed. In this study growth performance, Artemia intake, protein digestibility and protein retention were measured for Senegalese sole (Solea senegalensis Kaup), in order to provide insight into how protein utilization affects growth performance. Three feeding regimes were tested: ST – standard live feed; ArtRL – live feed and 20%Artemia replacement with inert diet (dry matter basis) from mouth opening; ArtRH – live feed and 58%Artemia replacement with inert diet from mouth opening. Artemia intake and protein metabolism were determined at 6, 15 and 21 days after hatching using 14C-labelled Artemia protein and subsequent incubation in metabolic chambers. At the end of the experiment, sole fed exclusively with live feed were significantly larger than sole from Artemia replacement treatments. Protein digestibility decreased during sole ontogeny, and more sharply in ArtRH sole. Concomitantly retention efficiency increased during ontogeny but with a slight delay in ArtRH sole. Senegalese sole larvae growth and protein utilization is depressed when co-fed high levels of inert diet and Artemia, mostly during metamorphosis climax.